Mencerdaskan Emosi Anak Usia Dini (AUD) Perspektif Wong Banyumas - Aziz, Safrudin (PIAUD Universitas Islam Negeri Sunan Kudus, 2018)
Emotional intelligence for early childhood can be done through various ways and certain stages. One of the most unique ways in educating children's emotions has been done by wong Banyumas. Efforts to educate the emotions of Wong Banyumas to children is done through the expression and implementation of attitude. Various expression wong Banyumas in educating the emotions of early childhood done in cablaka, blakasuta, thok melong and shrimp or give the pengalem. In terms of attitude, emotional intelligence is implanted through a critical attitude, uphold the equality in associating, visiting, be humorous to anyone, and inculcate the attitude of rikuh pekewuh. Educating emotion perspective wong Banyumas in the form of expression and planting attitude done naturally and unplanned. But the expression and implementation of attitude as an effort to educate emotion wong Banyumas in accordance with Goleman's theory that emotional intelligence is done through self-awareness planting, emotional management, recognizing the emotions of others, and fostering emotional relationships with others in harmony, all of which are contained in the phrase and implementation attitude of wong Banyumas.